Pelatihan Penggunaan Aplikasi Online sebagai Penunjang Model Pembelajaran Digital di Sekolah Dasar Swasta (SDS) Muhammadiyah Indonesiana Kota Tidore Kepulauan - Rosihan Rosihan; Hairil Kurniadi Siradjuddin; Yasir Muin; Ardi Salman; Rizki Pratama; Fatorahman A Saadu (Universitas 45 Surabaya, 2024)
Education is the cornerstone of a nation's development, and in facing the era of globalization and the Fourth Industrial Revolution, education in Indonesia must continue to transform. One crucial aspect is the implementation of information and communication technology (ICT) in the learning process. Elementary Schools (SD) as the initial stage of formal education are expected to utilize technological advancements, including the use of online applications, to enhance the effectiveness and quality of learning. The use of online applications as a support for digital learning in elementary schools is urgent due to several factors: Rapid Technological Development, Curriculum Demands, Limitations of Conventional Learning Resources, Importance of Digital Skills from an Early Age, and Parental Involvement in Learning.The Community Service Program of Khairun University at SDS Muhammadiyah Tidore involves the socialization and training in the use of online learning methods (e-learning) utilizing web tools such as Edpuzzle and Quizizz. This program is expected to provide sustainable solutions and contributions to the field of education by leveraging technological advancements. The implementation of this program aims to enhance the digital literacy of teachers and students at SDS Muhammadiyah Tidore, strengthen digital literacy, and create an innovative and interactive learning environment while maintaining ethical and professional values. Through this activity, educators are expected to adapt to technological developments in the field of education, reduce the digital divide between educators and students, and implement a more modern learning model. Continuous evaluation and the development of additional materials are expected to sustain the positive impact of this training in the long term.